Synergetic effects of hybrid nano-blended cement on mechanical properties of conventional concrete: Experimental and analytical evaluation. (February 2023) - Shahpari, Mehran; Khaloo, Alireza; Rashidi, Alimorad; Saberian, Mohammad; Li, Jie
Abstract: The present experimental and analytical study aims to modify conventional cement to create a higher strength-to-weight ratio concrete using hybrid nanomaterials, i.e., Carbon Nanotubes (CNTs) and Nano-Silica (NS), as a partial replacement for cement (Nano-blended cement). In this study, three CNTs and four NS contents were chosen to evaluate the mechanical properties of concrete. 234 tests for specimens at 7, 28, and 90 days were carried out to achieve the optimum composition of the nanoparticles for the compressive strength and splitting tensile strength. Test results of the specimens examined at 28 days illustrate that the compressive strength and tensile strength were improved by 125 % by the inclusion of 0.1 % CNT + 1.5 % NS and by 110 % by using 0.5 % CNT + 1.0 % NS, respectively. Moreover, the strength-enhancement mechanism of novel concrete was visualized by scanning electron microscopy (SEM). Since conventional high-performance concretes, due to the high amount of cement required, are not environmentally friendly, the novel Nano-blended cement can create high-performance concretes without adding more cement or any concrete ingredients. In addition, using Nano-blended concrete results in a lighter structure with smaller members' size and a more lightweight foundation, and therefore is more cost-effective and sustainable than conventional concrete.